2011
DOI: 10.1007/s00439-011-1064-z
|View full text |Cite
|
Sign up to set email alerts
|

The cell adhesion gene PVRL3 is associated with congenital ocular defects

Abstract: We describe a male patient (patient DGAP113) with a balanced translocation, 46,XY,t(1;3)(q31.3;q13.13), severe bilateral congenital cataracts, CNS abnormalities and mild developmental delay. Fluorescence in situ hybridization (FISH) and suppression PCR demonstrated that the chromosome 3 breakpoint lies ~515 kb upstream of the PVRL3 gene, while the chromosome 1 breakpoint lies ~50 kb upstream of the NEK7 gene. Despite the fact that NEK7 is closer to a translocation breakpoint than PVRL3, NEK7 transcript levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 65 publications
(74 reference statements)
0
47
0
Order By: Relevance
“…Mutations in human PVRL4 (which encodes nectin-4) that result in the failure of nectin-4 binding to nectin-1 cause an ectodermal dysplasiasyndactyly syndrome that is characterized by the combination of hair and tooth abnormalities, alopecia and cutaneous syndactyly (Brancati et al, 2010). Recent genome-wide association studies of various populations, including Japanese and African Americans, have shown a genetic association between singlenucleotide polymorphisms (SNPs) in PVRL2 (which encodes nectin-2) and late-onset alzheimer's disease (Harold et al, 2009;Logue et al, 2011;Takei et al, 2009), and mutations in PVRL3 (which encodes nectin-3) are associated with human ocular disease and congenital ocular defects (Lachke et al, 2012).…”
Section: Nectins In Human Diseasesmentioning
confidence: 99%
“…Mutations in human PVRL4 (which encodes nectin-4) that result in the failure of nectin-4 binding to nectin-1 cause an ectodermal dysplasiasyndactyly syndrome that is characterized by the combination of hair and tooth abnormalities, alopecia and cutaneous syndactyly (Brancati et al, 2010). Recent genome-wide association studies of various populations, including Japanese and African Americans, have shown a genetic association between singlenucleotide polymorphisms (SNPs) in PVRL2 (which encodes nectin-2) and late-onset alzheimer's disease (Harold et al, 2009;Logue et al, 2011;Takei et al, 2009), and mutations in PVRL3 (which encodes nectin-3) are associated with human ocular disease and congenital ocular defects (Lachke et al, 2012).…”
Section: Nectins In Human Diseasesmentioning
confidence: 99%
“…6.9b; Lachke et al 2012). On the other hand, E-and N-cadherins are expressed in the developing mouse lens (Cain et al 2008;Lachke et al 2012;Maddala et al 2011), where E-cadherin is localized at the cell-cell junction of the lens epithelial cells (Lachke et al 2012), and N-cadherin at the cell-cell junction of the fiber cells ( Fig. 6.9b; Maddala et al 2011).…”
Section: Heterotypic Adhesion: Formation Of Lensmentioning
confidence: 97%
“…F-actin is not depicted (Chow and Lang 2001;McAvoy 1980). All four nectin genes, Pvrl1, Pvrl2, Pvrl3, and Pvrl4 are expressed in the developing mouse lens (Lachke et al 2012;Okabe et al 2004a). Among them, nectin-1 is localized at the cell surface of the fiber cells adjacent to the lens epithelial cells (Lachke et al 2012;Maddala et al 2011), nectin-2 is distributed in both the lens epithelial and fiber cells (Okabe et al 2004a), and nectin-3 is localized at the apical surface of the lens epithelial cells, which face the fiber cells ( Fig.…”
Section: Heterotypic Adhesion: Formation Of Lensmentioning
confidence: 99%
See 2 more Smart Citations